Intergenerational income mobility in England and the importance of education - Pedro Carneiro; Sarah Cattan; Lorraine Dearden; Laura Van der Erve; Sonya Krutikova; Lindsey Macmillan (Institute for Fiscal Studies (IFS), 2022)
We use newly linked UK administrative to estimate absolute income mobility for children born in England in the 1980s. We find huge differences across the country, with a strong North-South gradient. Children from low-income families who grew up in the lowest mobility areas - overwhelmingly in the North - are expected to end up around fifteen percentiles lower in the income distribution as adults compared to those from the highest mobility areas - overwhelmingly in the South-East. Differences in average educational achievement across areas can explain 25% of this variation in absolute mobility within the country for men, and more than 45% of the variation for women. This indicates that education policy has an important role to play to equalise opportunities of children from low-income families across the country, though will not be sufficient to fully do so on its own. High mobility is further strongly related to stronger labour markets, more stable families, higher median income and better schools.
Keywords: J62; I24; I26; R00; 330; social mobility; human capital